THE CENOZOIC HISTORY OF THE CHUYA DEPRESSION (GORNY ALTAI): STRUCTURE AND GEODYNAMICS - Buslov M.M.; Zykin V.S.; Novikov I.S.; Delvaux D. (My University, 1999)
Detailed geological and geomorphological mapping of the transition zones from the Chuya depression to the surrounding mountains in the north (Kurai Range) and in the west (Chagan-Uzun block) allowed us to infer that both boundaries changed their evolution dynamics through time. The Chuya depression was initiated as a sedimentary basin bounded by uplifts in the Middle Miocene-Early Pleistocene and was then, apparently, a graben formed jointly with the neighboring Chagan-Uzun horst. The present-day structure of the depression has been produced by intense compression. In the latest Early Pliocene, the depression developed as a ramp basin, and in Late Pliocene and Quaternary time its northern boundary was rejuvenated by thrusting and transpression faulting. The Cenozoic history of the topography in southeastern Gorny Altai illustrates gradual progress of the deformation related to the India-Eurasia collision. As a result of this collision, since the Late Pliocene, the Altai orogen became separated from the Tuva-Mongolian microplate along a boundary following Late Paleozoic regional faults. The main regularities of the structure and evolution of the collisional boundary became evident owing to a special study, the results of which can be used in a description of similar neotectonic boundaries in Inner Asia.
Keywords: Cenozoic; Cenozoic; Кайнозой